Inference of Bubble Size Distribution in Sediments Based on Sounding by Chirp Signals - YANG, Xiaohong; ZHENG, Guangying; WANG, Fangyong; ZHU, Fangwei; BAI, Linlang (Archives of Acoustics, 2025)
A method is proposed to estimate the bubble void fraction and bubble size distribution in marine sediments based on measured sound speed and attenuation data in gas-bearing sediments. The new inversion approach employs an effective density fluid model, corrected for gas bubble pulsations, as the forward model and represents the unknown gas bubble size distribution using a finite sum of cubic B-splines. An in situ acoustic monitoring experiment was conducted at an intertidal site in the Yellow Sea to investigate gassy sediments and validate the method. The measured sound speed and attenuation show significant fluctuations due to bubble resonance, with resonance peaks shifting to higher frequencies as water depth and hydrostatic pressure increase. This method simultaneously estimates the bubble size distribution from sound speed and attenuation data.